Contamination of Salmonella spp. on Chicken Carcasses and their Risk Contributing Factors during Supply Chain in Jakarta - S. Shalihah; S. Nurjanah; Z. Wulandari (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2024)
The consumption of chicken meat by consumers in Jakarta is very high, which is in line with the high supply of it. Salmonella spp. is pathogenic bacteria which is frequently found in chicken carcasses and can cause food borne disease. The aims of this study were to determine the prevalence of Salmonella spp contamination on chicken carcasses and critical factors during distribution chain in Jakarta. The study was conducted based on the risk based approach compiled surveillance data, quantitative analysis of Salmonella spp., survey of good handling, constructed risk ranking and analysis sensitivity. Quantitative analysis determined by plate count method with using selective media XLT4 agar as Salmonella presumptive. Risk profile was involved risk-ranking and sensitivity analysis using Monte Carlo simulation of 100,000 iterations from Oracle Crystal Ball®. The highest prevalence of Salmonella in chicken carcasses is showed from traditional markets (41.86%) with amount was 1.09 ± 0.12 log CFU/g; then is followed from TPHU distribution (17.65%) with amount was 1.92± 1.11 log CFU/g. The risk contributing factors were the non-fulfillment of temperature of transportation from TPHU (12.3% contribution) and the unproper equipment’s cleaning method in traditional market (33.2% contribution). These were the most important aspects to be controlled.